Touch 'n Go: NPOs Effectiveness / Hasnatulsyakhira Abdullah Hadi, Fathiah Nuraina Amaran@Amran and Nurul Hidayana Mohd Noor - Abdullah Hadi, Hasnatulsyakhira; Amaran@Amran, Fathiah Nuraina; Mohd Noor, Nurul Hidayana (2021)
Visuals can be one of the methods to handle an extensive amount of information. Infographics may convey information about a topic more quickly and efficiently than plain text. TOUCH N' GO: NPOs EFFECTIVENESS is a set that combines QR codes and online quizzes in learning activities to provide students, lecturers, and NPO leaders with rapid and crucial information on NPOs effectiveness. The primary goal of this graphic visual is to increase the target audience's understanding of the efficacy of non-profit organizations. It may be used as a rapid reference guide as it is easy to be accessed with the emerging of technology as it assists NPOs leaders in providing information about effectiveness and this innovative approach is believed to make teaching and learning NPOs effectiveness courses easier, more fun, and faster, especially amid the Covid-19 epidemic.